Teachers’ perceptions of inclusive policy in education in private schools in Francistown, Botswana. - Kawonde, Tarisai (Midlands State University, 2018)
This is a qualitative study on Botswana private school teachers’ perceptions of the inclusion concept in the educational system. In this study, a case study was used as a strategy to conduct the practical aspects of this study. A study was the mixed method research design. Interviews and questionnaires were research tools that were used to collect data for this study. The sample comprised of 2 administrators and twenty teachers. A questionnaire on inclusion concept was developed on a five likert scale and administered to a stratified purposive sample of 20teachers in one private school in Francistown. All teachers responded to the questionnaire and their responses were coded, analysed using graphs and tables. The main findings for this study in general revealed that teachers in private schools have negative perceptions towards the concept of inclusion in the educational system. The findings of this study have significant implications to the school administrators, teachers and other stakeholders who are directly and indirectly involved in implementing inclusive education in Botswana.